Fine-tuning of polariton energies in a tailored plasmon cavity and J-aggregates hybrid system. Issue 45 (12th November 2020) - Liang, Kun; Guo, Jiaqi; Huang, Yuming; Yu, Li
Abstract : The fine-tuning of hybrid polariton states in a Au@Ag nanorod and J-aggregate strong coupling system by adjacent dielectric environment regulation is revealed. Abstract : Strong coupling systems enable coherent energy exchange between a light field and material electrons in nanoscale space. Active manipulation of this phenomenon by external stimuli is crucial for the design of advanced optoelectronic devices. Two neglected points severely hinder the improvement of tuning accuracy: irreversible variation in cavity morphology and lack of control over the dielectric environment which may change during the coupling process. Here we present a chemical fine-tuning of the strong plasmon–exciton coupling process in tailored Au@Ag nanocavities. The silver shell thickness was carefully controlled to tune the plasmon resonance wavelength with an accuracy of ∼8 nm and facilitate hot spots at the edges to boost the plasmon–exciton coupling strength. Hybrid polariton states were further regulated across the zero-detuning point with a spectral accuracy of less than 1 nm via tuning the solvent refractive index, and a Rabi splitting as large as 194 meV was observed at room temperature. The fine-tuning of strong plasmon–exciton coupling by an adjacent dielectric environment provides a novel route to manipulate excitons in molecules and possesses great potential for chemical or biological sensing.